326 DOES HYPERGAMMAGLOBULINEMIA PREDISPOSE PATIENTS WITH CHRONIC LYMPHOCYTIC LEUKEMIA TO SECONDARY SOLID TUMORS?. Issue 1 (1st January 2007) - Malani, A.; Singh, J.; Patel, V.; Skikne, B.; Pabla, M.; Vaka, S.; Gupta, C.; Vanveldhuizen, P.; Kambhampati, S.
Abstract : Background: Occurrence of second hematologic malignancies in patients with chronic lymphocytic leukemia (CLL) is well known, but development of secondary solid tumors has not been well documented. Isolated case reports indicate that CLL patients may have a predisposition to develop solid tumors. There is not enough literature available to support this hypothesis. We here intend to study the incidence of secondary solid tumors in CLL patients with regard to their treatment and immunoglobulin levels. Methods: We reviewed the medical records of 323 CLL patients over the last 20 years at Veterans Affairs Medical Center, Kansas City. Broadly, the patients were divided into two groups, the group that received chemotherapy for CLL (74/323) versus the group that did not receive treatment (249/323), and their median immunoglobulin levels were also documented. Patients who developed secondary hematologic malignancies were excluded from this study. Results: The overall incidence of solid tumors was found to be 14.8% (48/323). In the chemotherapy-treated CLL, the incidence of solid tumors was 18% (14/74) compared with 13.6% (34/249) in the nontherapeutic group ( p value .12). The most common malignancies noted were gastrointestinal malignancies, genitourinary tumors, and skin cancers, including melanomas. Interestingly, CLL patients who developed secondary solid tumors had a higher median IgG levels (1, 010 g/L) when compared with those who did not develop secondary tumors (738 g/L, p value < .003). Conclusion: Our study shows that there is a higher overall incidence of secondary solid tumors in patients with CLL when compared with the incidence in the general population. There is no significant increase in the incidence of therapy-related solid tumors in CLL patients. Upward drift in immunoglobulin levels should raise a suspicion for diagnosis of secondary solid tumors in patients with CLL. More studies are warranted to confirm this finding.